CTLA4-Ig (abatacept): a promising investigational drug for use in type 1 diabetes. (3rd March 2020) - Rachid, Ousama; Osman, Aisha; Abdi, Reza; Haik, Yousef
ABSTRACT: Introduction: Type 1 diabetes (T1D) is an autoimmune disease that results from the destruction of insulin-producing beta cells in the pancreas; it leads to the under or nonproduction of insulin. T1D is associated with numerous life-threatening micro- and macro-vascular complications and early deaths, hence the development of preventative strategies is a priority for research. Areas covered: The authors outline the drawbacks of available treatments for T1D and assess the three key strategies for prevention, including immunomodulatory therapies which hold the most potential. This article examines CTLA4-Ig and its efficacy and safety profiles. Finally, the pharmacokinetic parameters and pharmacodynamic markers of abatacept are shown in vivo and in clinical trials, guiding dosage regimen recommendations for future investigational studies. Expert opinion: Immunomodulation is one of the promising strategies for decelerating the progression of beta-cell destruction after the onset of T1D. It holds the advantage of specific immune modulation without systemic general immunosuppression. Preclinical and clinical studies have yielded promising data on the use of CTLA4-Ig in T1D. Variations in response to CTLA4-Ig might be partially explained by the existence of multiple T1D subtypes with varying baseline innate inflammatory/regulatory bias and the rate of C-peptide decline.